Comparison of the nutritional content of the captive and wild diets of the critically endangered mountain chicken frog (Leptodactylus fallax) to improve its captive husbandry. Issue 5 (17th September 2018) - Jayson, Stephanie; Ferguson, Amanda; Goetz, Matthias; Routh, Andrew; Tapley, Benjamin; Harding, Luke; Michaels, Christopher J.; Dawson, Jeff
Abstract : It is vital to provide appropriate nutrition to maintain healthy populations in conservation breeding programs. Knowledge of the wild diet of a species can be used to inform captive diet formulation. The nutritional content of the wild diet of the critically endangered mountain chicken frog ( Leptodactylus fallax ) is unknown, like that of most amphibians. In this study, we analyzed the nutritional content of food items that comprise 91% of the wild diet of L. fallax, by dry weight of food items, and all food items offered to captive L. fallax at ZSL London Zoo and Jersey Zoo. We subsequently compared the nutritional content of the wild diet and captive diet at ZSL London Zoo consumed by L. fallax . To the authors' knowledge, this is the first study to directly compare the nutritional content of the wild and captive diets of an anuran amphibian. The captive diet at ZSL London Zoo, without dusting of nutritional supplements, was higher in gross energy and crude fat and lower in ash, calcium and calcium:phosphorus ratio than the wild diet. Most of the food items in the captive diets had a high omega‐6:omega‐3 fatty acid ratio and in the wild diet had a low omega‐6:omega‐3 fatty acid ratio. We recommend a combination of modifications to the captive diets to better reflect the nutritional content of the wild diet. Nutritional analysis of captive and wild diets is recommended for other species in conservation breeding programs to improve captive husbandry and ultimately fitness.